FACTORS THAT INFLUENCE STUDENT STRES LEVELS IN COMPLETING THESIS USING ORDINAL LOGISTIK REGRESSION - Purwaningsi, Asih; Afandi, Fikry Wira; Saragih, Fani Imelda Br; Anggeraini, Maulida (Jurusan Matematika FMIPA Universitas Pattimura, 2025)
Environmental pressure that exceeds a person's capacity can cause stress. Writing a thesis at UINSU causes varying levels of stress. However, stress that cannot be determined will improve student performance. This study investigates the factors influencing the stress levels of thesis students at the State Islamic University of North Sumatra (UINSU) using ordinal logistic regression. The findings reveal that self-mootivation significantly increases stress levels by 2.6 times compared to students who do not consistently motivate themselves. The study provides insights intro how students can manage academic stress effectively.